Reduced rate of force development under fatigued conditions is associated to the decline in force complexity in adult males - Samuel D’Emanuele; Gennaro Boccia; Luca Angius; Oliver Hayman; Stuart Goodall; Federico Schena; Cantor Tarperi (European Journal of Applied Physiology, 2024)
Purpose This study aimed to verify whether the slowing of muscle contraction quickness, typically observed in states of fatigue, may worsen force control by decreasing the rate with which force fluctuations are modulated. Therefore, we investigated the relationship between rate of force development (RFD), and force fluctuations' magnitude (Coefficient of variation, CoV) and complexity (Approximate Entropy, ApEn; Detrended fluctuation analysis, DFAα). Methods Fourteen participants performed intermittent ballistic isometric contractions of the plantar dorsiflexors at 70% of maximal voluntary force until task failure (under 60% twice). Results Indices of RFD (RFD peak , RFD 50 , RFD 100 , and RFD 150 ) decreased over time by approximately 46, 32, 44, and 39%, respectively (p all ≤ 0.007). DFAα increased by 10% (p < 0.001), and CoV increased by 15% (p < 0.001), indicating decreased force complexity along with increased force fluctuations, respectively. ApEn decreased by just over a quarter (28%, p < 0.001). The linear hierarchical models showed negative associations between RFD peak and DFAα (β = − 3.6 10 –4 , p < 0.001), CoV (β = − 1.8 10 –3 , p < 0.001), while ApEn showed a positive association (β = 8.2 × 10 –5 , p < 0.001). Conclusion The results suggest that exercise-induced reductions in contraction speed, lead to smoother force complexity and diminished force control due to slower adjustments around the target force. The fatigued state resulted in worsened force producing capacity and overall force control.

Ischemic preconditioning of the muscle reduces the metaboreflex response of the knee extensors - Luca Angius; Benjamin Pageaux; Antonio Crisafulli; James Hopker; Samuele Maria Marcora (European Journal of Applied Physiology, 2022)
Purpose This study investigated the effect of ischemic preconditioning (IP) on metaboreflex activation following dynamic leg extension exercise in a group of healthy participants. Method Seventeen healthy participants were recruited. IP and SHAM treatments (3 × 5 min cuff occlusion at 220 mmHg or 20 mmHg, respectively) were administered in a randomized order to the upper part of exercising leg’s thigh only. Muscle pain intensity (MP) and pain pressure threshold (PPT) were monitored while administrating IP and SHAM treatments. After 3 min of leg extension exercise at 70% of the maximal workload, a post-exercise muscle ischemia (PEMI) was performed to monitor the discharge group III/IV muscle afferents via metaboreflex activation. Hemodynamics were continuously recorded. MP was monitored during exercise and PEMI. Results IP significantly reduced mean arterial pressure compared to SHAM during metaboreflex activation (mean ± SD, 109.52 ± 7.25 vs. 102.36 ± 7.89 mmHg) which was probably the consequence of a reduced end diastolic volume (mean ± SD, 113.09 ± 14.25 vs. 102.42 ± 9.38 ml). MP was significantly higher during the IP compared to SHAM treatment, while no significant differences in PPT were found. MP did not change during exercise, but it was significantly lower during the PEMI following IP (5.10 ± 1.29 vs. 4.00 ± 1.54). Conclusion Our study demonstrated that IP reduces hemodynamic response during metaboreflex activation, while no effect on MP and PPT were found. The reduction in hemodynamic response was likely the consequence of a blunted venous return.

Effects of caffeine on neuromuscular fatigue and performance during high-intensity cycling exercise in moderate hypoxia - Bruno P. C. Smirmaul; Antonio Carlos de Moraes; Luca Angius; Samuele M. Marcora (European Journal of Applied Physiology, 2017)

The effect of transcranial direct current stimulation of the motor cortex on exercise-induced pain - Luca Angius; James G. Hopker; Samuele M. Marcora; Alexis R. Mauger (European Journal of Applied Physiology, 2015)